Allelic imbalance at chromosome 17p13.3 (YNZ22) in breast cancer is independent of p53 mutation or p53 overexpression and is associated with poor prognosis at medium-term follow-up. - Thompson, A. M. (Nature Publishing Group, 1998)
Molecular and immunohistochemical studies of genetic events on chromosome 17p were prospectively compared with conventional clinical and pathological parameters and disease behaviour at a minimum of 72 months follow-up. In a series of 91 patients with primary operable breast cancer, 37 out of 91 (41%) patients had disease relapse and 23 out of 91 (25%) had died during the follow-up period. Allelic imbalance at the YNZ22 locus (17p13.3), demonstrated in 33 out of 63 (52%) informative patients, was significantly associated with disease recurrence (P < 0.01, 2 d.f. Cox analysis) and showed a trend towards impaired survival (P = 0.08, 2 d.f. Cox analysis) after a mean follow-up of 84 months for survivors. By contrast, p53 mutation (in 10 out of 60, 17% of cancers), p53 allelic imbalance (in 23 out of 56, 41% informative patients), p53 mRNA expression (in 47 out of 87, 54% patients), p53 mRNA overexpression (in 24 out of 87, 28%) or p53 protein expression (detected in 25/76, 32%) were not associated with disease behaviour. There was no significant association between allelic imbalance at YNZ22 and any abnormality of p53 DNA, RNA or protein. Allelic imbalance at 17p13.3 (YNZ22) serves as a marker of poor prognosis in breast cancer. As yet unidentified genes on 17p13.3, distinct from and telomeric to p53, are therefore likely to be of clinical importance in breast cancer.